Two Metrics Describing the Causes of Seasonal and Spatial Changes in Subglacial Aqueous Chemistry - Graly, Joseph A.; Humphrey, Neil F.; Licht, Kathy J. (Frontiers in Earth Science, 2018)
Seasonal change in surface melt input and spatial controls on the distribution of subglacial water can cause considerable variability in the aqueous chemistry of subglacial waters. Much of this variability has been interpreted in terms of a single variable: water residence time, with slow flow assumed to correlate with greater mineral dissolution and oxidative weathering. We synthesize data from a range of glacier and ice sheet settings to show that this approach does not adequately describe presently available data. Instead, we propose that two independent variables control spatial and seasonal changes in aqueous chemistry in subglacial settings: atmospheric gas abundance and sediment supply abundance. Where atmospheric gases are abundant, carbonation weathering is responsible for most of the subglacial chemical activity; where they become limited, oxidation weathering becomes more dominant. Where freshly comminuted sediment is abundant, easily dissolved minerals, especially calcite, have proportionally more influence on subglacial hydrochemistry; where sediment supply is limited, silicate minerals and less reactive carbonate minerals will increase in relative influence. In most settings, simple metrics of the abundance of SO42- and Ca2+ in the subglacial waters can characterize these two variables. In the data we synthesize, neither variable consistently correlates to the inferred water residence time, nor do the variables consistently correlate with each other. Spatial data show that point locations and small catchments on the glacial bed differ substantially from the integrated composition found at glacial outlets. The varied response in the subglacial aqueous chemistry to changing water residence times suggests complex control by a broad range of glaciological factors that affect water routing and subglacial sediment generation.